2011
DOI: 10.1007/s00572-011-0366-2
|View full text |Cite
|
Sign up to set email alerts
|

Ectomycorrhizal fungi in Mexican Alnus forests support the host co-migration hypothesis and continental-scale patterns in phylogeography

Abstract: To examine the geographic patterns in Alnus-associated ectomycorrhizal (ECM) fungal assemblages and determine how they may relate to host plant biogeography, we studied ECM assemblages associated with two Alnus species (Alnus acuminata and Alnus jorullensis) in montane Mexico and compared them with Alnus-associated ECM assemblages located elsewhere in the Americas. ECM root samples were collected from four sites in Mexico (two per host species), identified with ITS and LSU rRNA gene sequences, and assessed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 40 publications
5
69
0
5
Order By: Relevance
“…As in Pinaceae and Fagaceae, sebacinalean ECMs are present in Japanese mixed forests on Betula maximowicziana, B. grossa, and Carpinus japonica (Ishida et al 2007). Studies of ECMs in Mexican Alnus forests, supporting the host co-migration hypothesis, also included sebacinalean fungi (Kennedy et al 2011).…”
Section: Sebacinalean Ectomycorrhizae (Ecm)mentioning
confidence: 99%
“…As in Pinaceae and Fagaceae, sebacinalean ECMs are present in Japanese mixed forests on Betula maximowicziana, B. grossa, and Carpinus japonica (Ishida et al 2007). Studies of ECMs in Mexican Alnus forests, supporting the host co-migration hypothesis, also included sebacinalean fungi (Kennedy et al 2011).…”
Section: Sebacinalean Ectomycorrhizae (Ecm)mentioning
confidence: 99%
“…Later studies by Á gueda et al (2010), Buée et al (2009), De Román andDe Miguel (2005), García-Barreda and Reyna (2012), Genney et al (2006), Kennedy et al (2011a), Pickles et al (2010), Põlme et al (2013), Pritsch et al (2010), and Roy et al (2013) have confirmed this fact.…”
Section: How Ectomycorrhizal Types Share Root Systemsmentioning
confidence: 80%
“…Recent studies about the ectomycorrhizal fungal communities in alder forests on a local scale (Pritsch et al 2010), regional scale (Kennedy et al 2011a;Roy et al 2013), and global scale (Põlme et al 2013) show that they are not primarily rich, regardless of sampling intensity. The special characteristics of the Alnus spp.…”
Section: How Ectomycorrhizal Types Share Root Systemsmentioning
confidence: 99%
“…The thermocycler program was set for 94°C for 3 min (initiation and denaturation) followed by 35 cycles of 94°C for 1 min (denaturation), 50°C for 45 s (annealing), 72°C for 1.5 min (extension), with a final extension time of 10 min at 72°C. To verify the host of the sampled EcM roots, the primers trnL-c and trnL-d were used to amplify a region of the chloroplast DNA (Taberlet et al 1991) on amplified root tips for each tree sampled, following thermocycler conditions of Kennedy et al (2011). Amplification of DNA was confirmed by electrophoresis on 1 % agarose gels and visualized with GelRed (Biotium, Hayward, CA) under UV light.…”
Section: Methodsmentioning
confidence: 99%